Aplicação do Portfólio nas Escolas Médicas: Estudo de Revisão - Garcia, Maria Alice Amorim; Nascimento, Gabriela Egêa Alvaro Do (Associação Brasileira de Educação Médica, 2019)
ABSTRACT With the aim of producing professionals who are critical, creative and reflective, new proposals and reformulations have been created for Medical Education, based on an educational process that promotes the development of multiple skills. With the aim of guiding and improving students’ performance in the teaching-learning process, the portfolio provides support for reflection, broadening their reasoning skills, and combining theoretical knowledge – acquired in the classroom and through research – with experiences in services, territories and other learning scenarios. Encompassing information from different pedagogical strategies creates greater autonomy, self-evaluation, creativity, critical and intervention capacity. This article describes the application of the portfolio in Brazilian medical schools, based on a review of scientific publications and a survey of pedagogical projects via the internet. An integrative review of scientific articles from the period 2007 to 2017 was conducted in the databases of the Virtual Health Library (BVS), using the search terms Portfolio AND Medical Education, Portfolio AND Teaching, Portfolio AND Educational Assessment, and a survey of pedagogical projects published on the internet with quotations related to the portfolio. A total of 19 publications of investigations and 73 pedagogical access projects were found, 38 of which cited the word portfolio. A significant part of this work addresses the concepts of skills and narratives. It was found that portfolios are applied differently in each school, both as a means of reflection on the practice, and as a work file. The descriptions given relate to its application in certain disciplines, generally practices in services and communities and experiences in focal situations. Through the portfolio, situations are investigated and a search for and reflection on knowledge are stimulated. The exercise of a narrative that links practice with theory, facilitating students’ learning, is emphasized, as well as enhancing the confidence and ability of the student – who needs to make decisions in real, often complex situations – making him/her an active, critical individual, with greater autonomy, intervening in the reality. Comparing the number of pedagogical projects that cited the use of the portfolio with the number of publications found, it was concluded that there is a significant lack of studies that focus on the teaching-learning process in medical schools. Concerning the application of the portfolio, difficulties related to maintaining the biomedical model in schools, and traditional methods of teaching and evaluation, were highlighted, as well as the lack of motivation and conditions for teachers to engage in transformations that require training, cohesion and institutional support. With the lack of the teacher’s participation, and the excessive time taken to carry out the portfolio, the student is provided with with an instrument that encourages self-reflection and facilitates learning, but also faces difficulty breaking away from a traditional teaching model.

RESUMO Com o objetivo de formar um profissional crítico, criativo e reflexivo, novas propostas e reformulações vêm sendo criadas para o ensino médico, com base num processo educativo que promova o desenvolvimento de múltiplas competências. Buscando orientar a melhor atuação do estudante no processo ensino-aprendizagem, o portfólio fornece subsídios à reflexão, ampliando a capacidade de raciocínio, aliando o conhecimento teórico – adquirido em sala de aula e pesquisas – a vivências em serviços, territórios e demais cenários de aprendizagem. Englobando informações de diferentes estratégias pedagógicas, o portfólio possibilita maior autonomia, autoavaliação, criatividade, capacidade de crítica e de intervenção. Este estudo descreve a aplicação do portfólio nas escolas médicas brasileiras com base numa revisão de publicações científicas e do levantamento de projetos pedagógicos via internet. Procedeu-se a uma revisão integrativa de artigos científicos do período de 2007 a 2017, nas bases de dados da Biblioteca Virtual em Saúde (BVS), por meio dos descritores Portfólio AND Educação Médica, Portfólio AND Ensino, Portfólio AND Avaliação Educacional, e ao levantamento de projetos pedagógicos publicados na internet com citações referentes ao portfólio. Foram encontradas 19 publicações de investigações e 73 projetos pedagógicos acessíveis, entre os quais 38 citavam a palavra portfólio. Os conceitos de competências e narrativas permeiam parte expressiva dos trabalhos. Constatou-se que os portfólios são aplicados de forma muito diferenciada em cada escola, tanto como dispositivo de reflexão da prática, quanto como arquivo de trabalhos. As descrições referem-se à aplicação em determinadas disciplinas, em geral de práticas em serviços e comunidades e experimentos em situações focais. Por meio do portfólio, problematizam-se situações e estimula-se a reflexão e a busca de conhecimentos. Destaca-se o exercício da narrativa, que permite aliar a prática à teoria, facilitando a aprendizagem, além de ampliar a segurança e a habilidade do estudante – que precisa tomar decisões frente a situações reais, muitas vezes complexas –, fazendo com que este se torne um indivíduo ativo e crítico, com maior autonomia, intervindo na realidade. Comparando-se o número de projetos pedagógicos que citaram o uso do portfólio e as publicações encontradas, conclui-se que há grande carência de estudos voltados ao processo ensino-aprendizagem nas escolas médicas. Quanto aos achados a respeito da aplicação do portfólio, sobressaem as dificuldades relativas à manutenção do modelo biomédico nas escolas e métodos tradicionais de ensino e avaliação, bem como a falta de motivação e condições para que os docentes se dediquem a transformações que requerem capacitação, coesão e apoio institucional. Com a fragilidade na participação do professor e o excesso de tempo consumido na realização do portfólio, o estudante se depara com um instrumento que fomenta a autorreflexão e facilita seu aprendizado, mas também enfrenta a dificuldade de romper a barreira do ensino tradicional.
Application of the Portfolio in Brazilian Medical Schools: Integrative Review
Keywords: Portfolio; Education, Medical; Educational Measurement; Portfólio; Educação Médica; Avaliação Educacional